1996
DOI: 10.1524/ract.1996.72.4.179
|View full text |Cite
|
Sign up to set email alerts
|

Complexatíon of Trivalent Actinide Ions (Am3+, Cm3+) with Humic Acid: The Effect of Ionic Strength

Abstract: The effect of ionic strength on the complexatíon of Am 1+ and Cm 3+ by humic acid is investigated at pH 6 with three different experimental methods: ultrafiltration, UV-Visible spectroscopy, and time resolved laser fluorescence spectroscopy (TRLFS). The ionic strength is adjusted by NaCl0 4 and varied from 0.001 M to 5.0 M. The metal ion concentration is changed from 9.95 X10" 9 mol/L Cm 3+ to 1.04X 10" 5 mol/L Am 3+ , while the humic acid concentration is varied from 5.5 X10" 8 mol/L to 1.87 XI 0~5 mol/L. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
76
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 24 publications
6
76
1
Order By: Relevance
“…% of carbon, pH = 7.9 for GoHy-573; 0.080 g C/L, 56.6wt. % of carbon, pH = 7.8 for Gohy-2227), and W HA are available in [93,104] (4.91 × 10 −3 eq/g for Gohy-2227; 5.38 × 10 −3 eq/g for GoHy-573). The global interaction constant used is log GL HA β(Th 4+ ) = 21.3 from our present study.…”
Section: Validation On Independent Datamentioning
confidence: 99%
“…% of carbon, pH = 7.9 for GoHy-573; 0.080 g C/L, 56.6wt. % of carbon, pH = 7.8 for Gohy-2227), and W HA are available in [93,104] (4.91 × 10 −3 eq/g for Gohy-2227; 5.38 × 10 −3 eq/g for GoHy-573). The global interaction constant used is log GL HA β(Th 4+ ) = 21.3 from our present study.…”
Section: Validation On Independent Datamentioning
confidence: 99%
“…Humic substances have experimentally been shown to strongly complex the trivalent actinides (Artinger et al, 1998;Czerwinski et al, 1996;Morgenstern et al, 2000); Th(IV) (Nash and Choppin, 1980); U(VI) and probably U(IV) (Czerwinski et al, 1994;Zeh et al, 1997); and Np(V) (Kim and Sekine, 1991;Marquardt and Kim, 1998;Marquardt et al, 1996;Rao and Choppin, 1995) at mildly acidic to neutral pH. Under basic conditions, actinide-humic substance complexation is strongly a function of the carbonate concentration, because carbonate competes effectively with the humic acid as a ligand (Unsworth et al, 2002;Zeh et al, 1997).…”
Section: Microbial and Humic Colloidsmentioning
confidence: 99%
“…Little data are available for tetravalent actinides, but Tipping (1993) suggests, based on thermodynamic modeling, that these should be even more strongly complexed by humic substances than other oxidation states. Several studies have shown that actinide-humic acid complexes are thermodynamically stable in high ionic strength solutions (Czerwinski et al, 1996;Labonne-Wall et al, 1999;Marquardt et al, 1996). However, destabilization of humic colloids at high ionic strength (Buckau et al, 2000) and competition for humic acid sites by divalent metal cations (Marquardt et al, 1996;Tipping, 1993) may limit the importance of colloidal transport of actinides in brines.…”
Section: Microbial and Humic Colloidsmentioning
confidence: 99%
“…Humic colloids are stable and occur in concentrations up to 0.4 g L -1 in dilute, shallow groundwaters overlying the Gorleben test site in Germany (Buckau et al, 2000). Humic substances have experimentally been shown to strongly complex the trivalent actinides (Czerwinski et al, 1996;Artinger et al, 1998;Morgenstern et al, 2000); Th(IV) (Nash and Choppin, 1980); U(VI) and probably U(IV) (Czerwinski et al, 1994;Zeh et al, 1997); and Np(V) (Kim and Sekine, 1991;Rao and Choppin, 1995;Marquardt et al, 1996;Marquardt and Kim, 1998) at mildly acidic to neutral pH. Under basic conditions, actinidehumic substance complexation is strongly a function of the carbonate concentration, because carbonate competes effectively with the humic acid as a ligand (Zeh et al, 1997;Unsworth et al, 2002).…”
Section: Microbial and Humic Colloidsmentioning
confidence: 99%
“…Several studies have shown that actinide-humic acid complexes are thermodynamically stable in high ionic strength solutions (Czerwinski et al, 1996;Marquardt et al, 1996;Labonne-Wall et al, 1999). However, destabilization of humic colloids at high ionic strength (Buckau et al, 2000) and competition for humic acid sites by divalent metal cations (Tipping, 1993;Marquardt et al, 1996) may limit the importance of colloidal transport of actinides in brines.…”
Section: Microbial and Humic Colloidsmentioning
confidence: 99%